The Effect of Digital Marketing and Customer Satisfaction on Company Image And Its Impact on Customer Loyalty Local Water Supply Utility (PDAM) Semarang Regency - Yahya Yahya; Harry Soesanto (Return : Study of Management, Economic and Bussines, 2023)
Water, as a vital element needed by all living entities, including humans, is an irreplaceable staple in today's global ecosystem. Its presence has a crucial role in maintaining human survival. As a result, the responsibility for overall water management falls on the government as the main regulator in this regard. The basis for this research is due to the research gap and to strengthen theories about digital marketing on customer satisfaction and digital marketing and customer satisfaction on company image. The research method used is "explanatory research" which highlights the influence between research factors through hypothesis testing. Researchers distributed 180 questionnaires to 180 respondents from the draw. One hundred and thirty questionnaires were then examined for completeness until it showed that only 151 questionnaires had data suitable for use for research. The results showed that by increasing PDAM customer loyalty, an appropriate marketing method is needed using digital marketing methods. Customer loyalty is built on two variables, namely customer satisfaction and company image. The increasing number of customer complaints shows a decrease in the level of customer satisfaction of PDAM Semarang Regency. Efforts to reduce customer complaints are carried out through communication with customers.